2004
DOI: 10.1063/1.1758699
|View full text |Cite
|
Sign up to set email alerts
|

A stimulated emission pumping study of the first excited singlet state of germylidene (H2C=Ge)

Abstract: The A (1)A(2) states of H(2)CGe and D(2)CGe have been explored for the first time by A-X laser-induced fluorescence (LIF) spectroscopy of the orbitally forbidden S(1)-S(0) transition and stimulated emission pumping (SEP) and wavelength resolved fluorescence studies of the allowed B-A electronic transition. Medium-resolution SEP studies gave the excited A state nu(2), nu(3), nu(4), and nu(6) vibrational frequencies for H(2)C(74)Ge and D(2)C(74)Ge. The 4(1) and 6(1) levels and higher combination and overtone sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…On the basis of the potential energy surface obtained with the CCSD(T)//MP2/6-31G* method for the cycloaddition reaction between singlet Cl 2 Ge=Ge: and formaldehyde, it can be predicted that the dominant reaction pathway of the cycloadditional reaction is reaction (4). It consists of three steps , the first step is that the two reactants (R1, R2) form a four-membered Ge-heterocyclic ring germylene (INT3), which is a barrier-free exothermic reaction of 170.7 kJ/mol; the second step is that the INT3 further reacts with formaldehyde (R2) to form an intermediate (INT4), which is also a barrier-free exothermic reaction of 132.1 kJ/mol; the third step is that INT4 isomerizes to a spiro-Ge-heterocyclic ring compound (P4) via a transition state (TS4) with an energy barrier of 57.3 kJ/mol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of the potential energy surface obtained with the CCSD(T)//MP2/6-31G* method for the cycloaddition reaction between singlet Cl 2 Ge=Ge: and formaldehyde, it can be predicted that the dominant reaction pathway of the cycloadditional reaction is reaction (4). It consists of three steps , the first step is that the two reactants (R1, R2) form a four-membered Ge-heterocyclic ring germylene (INT3), which is a barrier-free exothermic reaction of 170.7 kJ/mol; the second step is that the INT3 further reacts with formaldehyde (R2) to form an intermediate (INT4), which is also a barrier-free exothermic reaction of 132.1 kJ/mol; the third step is that INT4 isomerizes to a spiro-Ge-heterocyclic ring compound (P4) via a transition state (TS4) with an energy barrier of 57.3 kJ/mol.…”
Section: Resultsmentioning
confidence: 99%
“…In 1997, Clouthier et al 1 from University of Kentucky observed the first unsaturated germylene-germylidene, which is produced by striking an electric discharge in a high-pressure argon pulse using the tetramethylgermane (TMG) vapor as the precursor. They obtained its molecular structure and the ab initio predictions, 2 electronic spectrum 2 and oscillatory fluorescence decay 2 of jet-cooled germylidene (H 2 C=Ge:), and learnt the ground state 3 of H 2 C=Ge: and D 2 C=Ge:, the stimulated emission pumping (SEP) spectroscopy 4 of the first excited singlet state of germylidene. Stogner and Grev 5 have published the extensive ab initio calculations on both germylidene and the trans-bent germyne HCGeH isomer.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the potential energy profile obtained with the B3LYP/6-31G** method for the cycloaddition reaction between singlet dichlorosilylene germylidene (Cl 2 Si=Ge:) and acetone, it can be predicted that the dominant reaction pathway of the cycloadditional reaction is reaction (4). It consists of three steps: the first step is that the two reactants (R1, R2) form a Si-heterocyclic four-membered ring germylene (INT3), which is a barrier-free exothermic reaction of 198.2 kJ/mol.…”
Section: Resultsmentioning
confidence: 99%
“…The unsaturated germylene − germylidene was first produced by bombarding the tetramethylgermane (TMG) vapor using high-pressure steam pulse, which was found in 1997 by Clouthier group 1 of University of Kentucky. Ab initio study on the first unsaturated germylene − germylidene, they got this molecular structure, 2 electronic spectrum 2 and swinging fluorescence spectrum, 2 structure of its ground state, 3 and the stimulated emission pumping (SEP) spectroscopy 4 of the first excited singlet state of germylidene. Stogner and Grev have done extensive theoretical calculations 5 on germylidene and the trans-bent germyne HC ≡ GeH isomer with RHF/DZP and DHF/TZ(2df,2pd) method.…”
Section: Introductionmentioning
confidence: 99%
“…The popular hybrid density functional B3LYP method, namely Becke's three-parameter nonlocal exchange functional 26 with the nonlocal correlation functional of Lee, Yang, and Parr, 27 and 6-311+G* basis set including diffuse and polarization functions have been employed comprehensively. The B3LYP/6-311+G* level of theory has been proved relatively accurate to treat with the relevant insertion reactions in our previous study.…”
Section: Calculation Methodsmentioning
confidence: 99%